Anthelmintic Therapy Modifies the Systemic and Mycobacterial Antigen-Stimulated Cytokine Profile in Helminth-Latent Mycobacterium tuberculosis Coinfection - Anuradha, Rajamanickam (Infect Immun, 2017)
Helminth infections are known to modulate cytokine responses in latent tuberculosis (LTB). However, very few studies have examined whether this modulation is reversible upon anthelmintic therapy. We measured the systemic and mycobacterial (TB) antigen-stimulated levels of type 1, type 2, type 17, and regulatory cytokines in individuals with LTB and with or without coexistent Strongyloides stercoralis infection before and after anthelmintic therapy. Our data reveal that individuals with LTB and coexistent S. stercoralis infection have significantly lower levels of systemic and TB antigen-stimulated type 1 (gamma interferon [IFN-γ], tumor necrosis factor alpha [TNF-α], and interleukin-2 [IL-2]) and type 17 (IL-17A and/or IL-17F) cytokines and significantly higher levels of systemic but not TB antigen-stimulated type 2 (IL-4 and IL-5) and regulatory (transforming growth factor beta [TGF-β]) cytokines. Anthelmintic therapy resulted in significantly increased systemic levels of type 1 and/or type 17 cytokines and in significantly decreased systemic levels of type 2 and regulatory (IL-10 and TGF-β) cytokines. In addition, anthelmintic therapy resulted in significantly increased TB antigen-stimulated levels of type 1 cytokines only. Our data therefore confirm that the modulation of systemic and TB antigen-stimulated cytokine responses in S. stercoralis-LTB coinfection is reversible (for the most part) by anthelmintic treatment.